The Boundary Regularity of Pseudo-holomorphic Disks (Journal of Partial Differential Equations, 2001)
In this paper we will prove the continuity, the C^k-regularity after deforming suitably the domain, and the Hölder continuity, of the weakly pseudo-holomorphic disk with its boundary in a singular totally-real subvariety with only corners as its singularites.
Keywords: Pseudo-holomorphic disk; totally-real submanifold; continuity; Hölder continuity; corner